The History of Pesantren: An Overview of Civilizational Discourse and the Religious Moderation Among Santri - Choirur Rois; Marisa Santi Dewi; Nur Robaniyah (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2023)
Pesantren’s histories encompass pesantren as a forum for da’wah, an educational institution, and as a habitus of Islamic moderation civilization in Indonesia. This article aims to explore and reveal the track record of pesantren’s historicity from two sides: First, how the scientific sanad of the Yellow Book and the theological, fiqh, and Sufi are reasoning used to inform the discourse of pesantren civilization. Second, how pesantren serve as the pillars of a moderate Islam. This research used qualitative methodologies and a histography approach of pesantren and was presented using descriptive analysis. The results of this research suggest that in the 21st century AD, the discourse of pesantren created the construction of civilizational fiqh as a dialogue discourse on the social conditions today with narratives of contemporary fiqh understanding as a reflection of civilization. The learning tradition in pesantren contributes to the distribution of religious and pesantren intellectuals who are proven to be able to make an essential contribution in caring for Indonesia become unity.